Does stretching increase ankle dorsiflexion range of motion? A systematic review. Issue 10 (22nd August 2006) - Radford, J A; Burns, J; Buchbinder, R; Landorf, K B; Cook, C
Abstract : Background: Many lower limb disorders are related to calf muscle tightness and reduced dorsiflexion of the ankle. To treat such disorders, stretches of the calf muscles are commonly prescribed to increase available dorsiflexion of the ankle joint. Hypothesis: To determine the effect of static calf muscle stretching on ankle joint dorsiflexion range of motion. Study design: A systematic review with meta-analyses. Methods: A systematic review of randomised trials examining static calf muscle stretches compared with no stretching. Trials were identified by searching Cinahl, Embase, Medline, SportDiscus, and Central and by recursive checking of bibliographies. Data were extracted from trial publications, and meta-analyses performed that calculated a weighted mean difference (WMD) for the continuous outcome of ankle dorsiflexion. Sensitivity analyses excluded poorer quality trials. Statistical heterogeneity was assessed using the quantity I 2 . Results: Five trials met inclusion criteria and reported sufficient data on ankle dorsiflexion to be included in the meta-analyses. The meta-analyses showed that calf muscle stretching increases ankle dorsiflexion after stretching for ⩽15 minutes (WMD 2.07°; 95% confidence interval 0.86 to 3.27), >15–30 minutes (WMD 3.03°; 95% confidence interval 0.31 to 5.75), and >30 minutes (WMD 2.49°; 95% confidence interval 0.16 to 4.82). There was a very low to moderate statistical heterogeneity between trials. The meta-analysis results for ⩽15 minutes and >15–30 minutes of stretching were considered robust when compared with sensitivity analyses that excluded lower quality trials. Conclusions: Calf muscle stretching provides a small and statistically significant increase in ankle dorsiflexion. However, it is unclear whether the change is clinically important.